Re-thinking Project-Based Learning and Intrapersonal Intelligence at Kindergarten Talitakum: Can Early Learners Reflect? - Neni Riskayanti; Yanni Paembonan (Program Studi Pendidikan Islam Anak Usia Dini, 2026)
This study seeks to examine how project-based learning can be applied to enhance intrapersonal intelligence among children in the Kindergarten Talitakum. The approach utilized is classroom action research, following the Kemmis and McTaggart model, which involves a cycle consisting of four key components: planning, action, observation, and reflection or evaluation. The students in Kindergarten B class were 18 children. The study's findings indicated that during the observation process in cycles 1 face-to-face 1 and 2, the data showed that only 31.25% of the children, which is 6 out of 18, exhibited an active response in face-to-face 1. The results from cycle 1 face-to-face session 2 showed that 59.38%, which is 11 out of 18 children, achieved the outcome. In cycle 2, when children were grouped for the implementation of Project Based Learning, the data showed that 84.37% of the children, which is 15 out of 18, were actively participating in class. Additionally, 15.63% of the children, or 3 out of 18, were quite active during the sessions. Thus, the use of project-based learning can enhance children's intrapersonal intelligence when it is integrated into group learning activities.